2006
DOI: 10.1097/01.ccm.0000218412.86977.40
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sedative infusion requirements and permissive hypercapnia in critically ill, mechanically ventilated patients*

Abstract: We conclude that higher doses of propofol but not midazolam are required to sedate patients managed with PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 24 publications
(25 reference statements)
0
11
2
2
Order By: Relevance
“…An assumption was made that the ICU team managing each patient would titrate all sedative (and opioid) therapy toward a level of sedation that would help facilitate oxygenation and permit the use of mechanical ventilation with a low tidal volume. 5,13,27 The maximum amount of sedation administered in any 6-hour period was therefore deemed, for the purposes of the study, to reflect the time during each patient's ICU stay during which sedative therapy first reached the desired therapeutic sedation goal and served as the primary outcome for the investigation. This 6-hour window was based on the expected high frequency of benzodiazepine infusion use in the study population and has been used to characterize periods of ICU sedative exposure in other studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An assumption was made that the ICU team managing each patient would titrate all sedative (and opioid) therapy toward a level of sedation that would help facilitate oxygenation and permit the use of mechanical ventilation with a low tidal volume. 5,13,27 The maximum amount of sedation administered in any 6-hour period was therefore deemed, for the purposes of the study, to reflect the time during each patient's ICU stay during which sedative therapy first reached the desired therapeutic sedation goal and served as the primary outcome for the investigation. This 6-hour window was based on the expected high frequency of benzodiazepine infusion use in the study population and has been used to characterize periods of ICU sedative exposure in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum amount of sedation administered in any 6‐hour period was therefore deemed, for the purposes of the study, to reflect the time during each patient's ICU stay during which sedative therapy first reached the desired therapeutic sedation goal and served as the primary outcome for the investigation. This 6‐hour window was based on the expected high frequency of benzodiazepine infusion use in the study population and has been used to characterize periods of ICU sedative exposure in other studies . Other important sedation‐related secondary outcomes compared between the two groups included the time to reach the maximum amount of sedation administered, the total cumulative amount of sedation administered to reach this maximum, and the total cumulative amount of sedation administered during the defined period of data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Permissive hypercapnia, however, is not an absolute consequence of a lung-protective ventilation strategy, because the respiratory rate can be increased to reduce PaCO 2 . This practice was not followed in the study by Vinayak and colleagues [58], perhaps resulting in unnecessary hypercapnia in their low tidal volume group. Cheng and colleagues [59] examined the effects of tidal volume selection on supportive therapies in a retrospective analysis of data from the ARDSNet trial and found that a tidal volume of 6 mL/kg compared with 12 mL/kg did not result in increased need for vasopressors, intravenous fluids, or diuretics.…”
Section: Sedation and Paralysismentioning
confidence: 95%
“…There is concern related to the need for additional sedation in patients receiving low tidal volumes, supported by Vinayak and colleagues [58], who retrospectively studied the relationship between sedative infusion requirements and permissive hypercapnia in critically ill, mechanically ventilated patients. They reported that higher doses of propofol, but not midazolam, were required to sedate patients managed with permissive hypercapnia.…”
Section: Sedation and Paralysismentioning
confidence: 97%
“…The study design allowed physiological parameter assessment in a condition of steady-state because remifentanil plasma levels stabilize within 10 minutes from the start of a constant rate iv infusion and the half-time for equilibration between plasma and its effect compartment is about 1-1.5 min [46,47]. reviewed 124 mechanically ventilated, critically-ill patients that underwent sedation with propofol or midazolam and received morphine for analgesia [48]. Infusion rates over 6 mcg/Kg/h caused 4 patients to exit the study because of hypoventilation, which was defined as "no breathing activity registered during 15 sec or a reduction of minute ventilation to values lower than 60% of basal values" Fig.…”
Section: Controlled Mechanical Ventilationmentioning
confidence: 99%